THE EFFECT OF IMPLEMENTING CHSE ON GUESTSATISFACTION AT MIE GACOAN TEGAL - Sabrina, Tantri Adithia; Anggraeni, Puput Dewi (UI Scholars Hub, 2021)
The spread of Covid-19 at the end of 2019 from one region to another region, until spreading all over the world. In March 2020 WHO deciding Covid-19 as pandemic. The spread of Covid-19 through droplets because of that goverment decides crowds rectriction. Various fields aver the world adapting to this pandemic. Goverment through Kemenparekraf (Indonesians Ministry of Tourism and Creative Economy) compiling manual guidebook that regulates various activities. The guidebook contents about CHSE guide. This guide is mandatory to all restaurant. The implementation of CHSE affects guast from all aspects. The purpose of this study was to determine the effect of implementing CHSE on guest satisfaction pasticularly at Mie Gacoan Tegal. The research method used quantitatif study with incidental sampling technic. Data collection using questionnaire and analyzed using simple regression analysis. The result of this study found that implementing CHSE has a positive effect on guests satisfaction. Researcher suggestion for restaurants management is to consisten appliying CHSE and always updating about Covid-19.